Peran Majelis Pengawas Notaris Terhadap Laporan Masyarakat (Studi Kasus Putusan MPPN Nomor 02/B/MPPN/X/2018) - Karinda, Yoel Charlye (Notary Journal, 2023)
In the event that there is a public report on alleged violations committed by a notary, the Notary Supervisor Assembly plays an important role in handling the complaint based on the principles and provisions of the applicable complaint handling legislation. In this case, the Notary Supervisor Assembly examines reporter and reported party, examines the legal facts, and makes legal considerations to decide the sanctions to be given. As in the decision of the Notary Center Supervisor Assembly (MPPN) Number 02/B/MPPN/X/2018, the Notary is reported for alleged violations that are detrimental to the reporter party. This is a solid reason to examine the role of the Notary Supervisor Assembly in handling complaints and the legal consequences of decisions issued. Therefore, a research was conducted to examine this issue. The reseacher applied normative law with a statute approach. The data used is secondary data supported by primary data. The secondary data obtained from library materials, while primary data obtained through interviews. Data analysis was examined with quantitative approach which resulted in descriptive analysis. The results of this study shows that the role of the Supervisory Assembly on public reports is regulated in UUJN P Article 70 letter G and the Regulation of the Minister of Law and Human Rights Number 15 of 2020 concerning Procedures for Examination of the Supervisory Assembly on Notaries. The legal consequence of the decision of the Regional Assembly is a verbal warning to the notary. Meanwhile, the legal consequence of the decision of the Center Supervisory Assembly is to strengthen the decision of the Regional Supervisory Assembly, so as to produce a final decision.Bahasa Indonesia Abstrak: Dalam hal adanya laporan masyarakat terhadap dugaan pelanggaran yang dilakukan oleh Notaris, maka Majelis Pengawas Notaris mempunyai peran penting dalam menerima penanganan pengaduan tersebut berdasarkan prinsip-prinsip penanganan pengaduan berdasarkan ketentuan perundang-undangan yang berlaku. Dalam hal ini Majelis Pengawas Notaris memeriksa antara pelapor dan terlapor, menemukan fakta-fakta hukum, dan membuat pertimbangan hukum untuk memutuskan sanksi apa yang akan diberikan kepada Notaris. Seperti pada putusan Majelis Pengawas Pusat Notaris (MPPN) No. 02/B/MPPN/X/2018, dalam putusan tersebut Notaris dilaporkan atas dugaan pelanggaran yang merugikan pelapor. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana peran Majelis Pengawas Notaris dalam proses penanganan pengaduan sampai ke tahap keputusan yang diberikan. Untuk menjawab hal tersebut maka dilakukan penelitian secara normatif dengan pendekatan undang-undang (statute approach). Data yang digunakan adalah data sekunder didukung dengan data primer. Data sekunder yang diperoleh dari bahan-bahan kepustakaan data primer diperoleh melalui wawacara dan analisis data secara kualitatif yang menghasilkan deskriptif analisis. Dari hasil penelitian, Peran Majelis Pengawas terhadap laporan masyarakat diatur diatur dalam UUJN P Pasal 70 huruf g dan Peraturan Menteri Hukum dan Hak Asasi Manusia Nomor 15 Tahun 2020 tentang Tata Cara Pemeriksaan Majelis Pengawas terhadap Notaris. Akibat hukum terhadap putusan Majelis Wilayah adalah penerapan sanksi teguran lisan terhadap Notaris, dan akibat hukum terhadap putusan Majelis Pengawas Pusat adalah menguatkan Putusan dari Majelis Pengawas Wilayah, sehingga keputusan dari Majelis Pengawas Pusat adalah final.